ETIKA KERJA ISLAM DAN PERILAKU “VOICE” PROSOSIAL GURU: MEKANISME IDENTIFIKASI ORGANISASI - Purnamasari, Nita; Abdillah, M.Rasyid; Anita, Rizqa (Yayasan Education and Social Center, 2025)
This study aims to determine the influence of teacher voice propionality and Islamic work ethics on teacher performance with organizational commitment. The location of this research was carried out in three Madrasyah Aliyah (MA) schools in the Tembilahan area, namely M.A Sabilal Muhtadin, M.A Pondok Pesatren Tunas Harapan (PPTH), M.A Nurul Jihad, M.A Miftahul Huda, M.A Jami'atul Islamiyah and M.A Negeri Tembilahan. The population in this study is all Madrasyah Aliyah (MA) teachers in the Tembilahan area, namely M.A Sabilal Muhtadin, M.A Pondok Pesatren Tunas Harapan (PPTH), M.A Nurul Jihad, M.A Miftahul Huda, M.A Jami'atul Islamiyah and M.A Negeri Tembilahan which totals 200 people. The sampling method used in this study is a saturated sample or census with the entire population as a sample. So the sample in this study is 200 Madrasyah Aliyah (MA) teachers in the Tembilahan area, namely M.A Sabilal Muhtadin, M.A Pondok Pesatren Tunas Harapan (PPTH), M.A Nurul Jihad, M.A Miftahul Huda, M.A Jami'atul Islamiyah and M.A Negeri Tembilahan. The data analysis technique in this study uses the equation Structural Equation Model (SEM) Partial Least Square (PLS) SEM-PLS with Smart PLS Software. The PLS-SEM Outer Model analysis consists of Convergent Validity Test, Discrimination Validity Test, and Composite Reliability, while the Inner Mode consists of R-Square, and Goodness of Fit, then Path Analysis, and Hypothesis Test. The result of this study is that the teacher's proportional